Pengaruh Perubahan Material Penampang Saluran Irigasi Terhadap Luas Areal Layanan Daerah Irigasi Gumbasa - Frida Sulistyani, Kiki ; Bimo Irianto, Danang (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The Palu earthquake in September 2018 caused damage in various sectors, the GumbasaIrrigation Network was also damaged and will be repaired, repairs in primary canal werecarried out along 36,047 km using concrete material on the side and bottom of thechannel.Gumbasa Irrigation Networks has 8180 Ha service area ,and has 40 tapping structure,2 split structure and 16 split tapping structure. With the change of channel material in theprimary channel, the water level decreased between 5 cm - 55 cm, from 40 tapping structure inthe primary channel only 4 tapping structure that can still deliver water to their service area,there has been a reduction in service area from 2965 Ha to 50.2 Ha, and from 18 secondarychannels, there is only 1 that cannot supplay water into its service area, while others can stillflow even if it is not according to needs, there is a decrease in service area from 5215 Ha to2948 ha. So overall with the change in channel material from soil to concrete, the service areain Gumbasa decreased from 8180 Ha to 2998 Ha or 36.7% of the planned service area. Thiscan be resolved by raising the base of the channel between 5 cm - 55 cm,or changing thedimensions and sloope of the channel